Application of shared care management model in type 2 diabetes - YANG Ting*, YU Yong, HAN Jing, CAO Dan, HU Lin, LYU Yingqi (Zhongguo linchuang yanjiu)
Objective To assess the impact of the shared care management model on control levels of blood glucose, blood lipid and blood pressure in patients with type 2 diabetes mellitus (T2DM). Methods From July 2020 to February 2024, 873 T2DM patients were prospectively recruited to participate in the shared care management model in Zhongda Hospital, Southeast University. The online activity of patients was comprehensively evaluated by chatting frequency, uploading diet records and self-blood glucose monitoring records, and APP login frequency, and the patients were divided into online active and online inactive according to the median. According to whether the number of offline visits exceeded 2 in a year, the patients were divided into offline active and offline inactive. Multivariate logistic regression analysis was used to determine the influencing factors for hemoglobin A1c(HbA1c) up to the standard after one year. Results Compared with online-inactive patients, online-active patients had younger age (P＜0.01), shorter disease duration (P＜0.01), lower HbA1c level (P＜0.01), higher HbA1c compliance rate (75.6% vs 66.6%, χ2=8.228，P=0.004), lower diastolic blood pressure ［76.0(70.0, 78.0) mmHg vs 76.0 (71.0, 80.0) mmHg, Z=3.392, P=0.001］, and higher blood pressure compliance rate (64.7% vs 55.8%, χ2=6.831, P=0.009), lower triglyceride level ［1.2 (0.8, 1.9) mmol/L vs 1.5 (1.0, 2.5) mmol/L, Z=2.606, P=0.009］, higher high-density lipoprotein cholesterol level ［1.2 (1.1, 1.3) mmol/L vs 1.1 (0.9, 1.3) mmol/L, Z=2.834, P=0.005］. Multivariate logistic regression analysis showed that integrated in-person and remote care, shorter diabetes duration, and lower baseline HbA1c levels were more conducive to the patients' reaching the standard of HbA1c after one year of follow-up (P＜0.05). Conclusion Compared to the traditional offline-only management model, the shared care management model demonstrates significant benefits for managing T2DM patients. The shared care management model could improve HbA1c levels and increase the likelihood of reaching target rates, offering a new pathway for advancing the standardized clinical management of diabetes.